Analisis Sentimen Pendapat Netizen Indonesia Terhadap Pengungsi Rohingya Pada Aplikasi X Menggunakan Algoritma Naive Bayes - Lestari, Putri; Irwiensyah, Faldy (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2024)
Rohingya ethnic group is one of the victims of genocide atrocities committed by Myanmar as a result of past grudges. Because of this, several ethnic groups chose to leave Myanmar and decided to flee to other countries, including Indonesia, as a result, this issue continued to rise on social media. This research was conducted with the aim of analyzing public opinion sentiment regarding the inclusion of the Rohingya ethnic group on social media X using the Naive Bayes method. The data carried out using the Web Scrapping method was 1124 with a time span of May 2023 to January 2024 and the data was continued with the preprocessing stage and removing duplications in the data which made the data change to 701. After going through these stages it can be implemented into Naive Bayes. The results of implementing Naive Bayes in this research about the opinions of Indonesian netizens regarding Rohingya refugees in the X application obtained an accuracy value of 98.57%, precision 100%, and recall 97.35%.